Pemberdayaan Karang Taruna Dalam Pengolahan Sampah Botol Plastik Menjadi Paving Block Dengan Mesin ATM Sampah - syahputra, Rendy; Sutrisno, Agung; Riogilang, Herawaty (STMIK Royal, 2025)
This community service activity aims to reduce the environmental impact of plastic bottle waste by turning it into an economically valuable product, namely paving blocks. Plastic waste, especially plastic bottles, is one of the biggest contributors to environmental pollution. This program uses a collaborative governance method that involves Buha Village officials, thus the surrounding community is given education and training on how to process plastic bottle waste into paving blocks, starting from collection, shredding, mixing with materials such as sand and cement, to the printing process. The results of this activity show that the paving blocks produced have strength and quality that are suitable for light construction. In addition to reducing the amount of plastic waste, this program also opens up business opportunities for the local community. The active participation of the community in this program has a positive impact on increasing environmental awareness and local economic welfare. The community will collect plastic bottle waste through a waste Automatic Teller Mechine machine which will later become the basis for calculating royalties from the sale of paving blocks. The recycling process that has been carried out from plastic waste into paving blocks is very beneficial for the community and the environment itself.Keywords: plastic waste; paving blocks; waste management;environment Abstrak: Kegiatan pengabdian masyarakat ini bertujuan untuk mengurangi dampak lingkungan dari limbah botol plastik dengan mengubahnya menjadi produk yang bernilai ekonomis, yaitu paving block. Limbah plastik, khususnya botol plastik, menjadi salah satu penyumbang terbesar dalam pencemaran lingkungan. Program ini menggunakan metode collaborative governance yang melibatkan perangkat Kelurahan Buha, dengan demikian masyarakat sekitar diberikan edukasi dan pelatihan tentang cara pengolahan limbah botol plastik menjadi paving block, mulai dari pengumpulan, pencacahan, pencampuran dengan bahan-bahan seperti pasir dan semen, hingga proses pencetakan. Hasil dari kegiatan ini menunjukkan bahwa paving block yang dihasilkan memiliki kekuatan dan kualitas yang layak digunakan untuk konstruksi ringan. Selain mengurangi jumlah sampah plastik, program ini juga membuka peluang usaha bagi masyarakat setempat. Partisipasi aktif masyarakat dalam program ini memberikan dampak positif terhadap peningkatan kesadaran lingkungan dan kesejahteraan ekonomi lokal. Masyarakat akan mengumpulkan sampah botol plastic melalui mesin Automatic Teller Mechine sampah yang nantinya menjadi dasar perhitungan royalty dari penjualan paving block. Proses daur ulang yang telah dilakukan dari sampah plastik menjadi paving block sangat bermanfaat bagi masyarakat dan lingkungan.Kata kunci: limbah plastik; paving block; pemberdayaan masyarakat